PENGARUH CORPORATE GOVERNANCE, KARAKTER EKSEKUTIF, INSENTIF EKSEKUTIF DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Samung Wuwur, Andreas (Soetomo Accounting Review, 2024)
The objective of this research to analyze the factors that have an impact to tax avoidance. Independent factors that used in this research consists of corporate governance, executives character, executives incentives and leverage. Samples on this research is all of manufacturing companies that listed in Indonesian Stock Exchange (BEI) in the period 2016-2019. Sampling method using purposive sampling with criterias that setted by researcher and got 168 companies as the samples. Method of data analysis using multiple regression analysis and use software assisted Statistical Package for Social Sciences (SPSS) version 23. The results of this research are corporate governance has a negative significant influence to tax avoidance, executives incentives has a positive significant influence to tax avoidance, while executives character and leverage have not significant influence to tax avoidance .